Correlation among Academic Procrastination, Personality Traits, and Academic Achievement - Karatas, Hakan (KAMLA-RAJ ENTERPRISES, 2015)
Procrastination is explained as a complex phenomenon with cognitive, affective, and behavioral components consisting of the intentional postponement of an intended course of action in spite of awareness of possible negative consequences. Procrastination on academic tasks is a common problem affecting learning and achievement of university students and may have an effect on students' personality traits and their learning because it affects the self-efficacy, self-control, and organizational behavior of the students. Personality is regarded as an important individual resource in academic settings and plays an important role in students' academic performance. Academic procrastination and personality traits are regarded as important factors affecting learning and achievement of university students, and has a strong link with them. In this study, the findings on the correlation of academic procrastination, personality traits, and academic achievement in a sample of university students are presented.
Keywords: Procrastination; Big Five Traits; Individual Differences; Undergraduates; Academic Achievement; 5-FACTOR MODEL; INDIVIDUAL-DIFFERENCES; COGNITIVE-ABILITY; SELF-REGULATION; PERFORMANCE; PREDICTORS; MOTIVATION; STUDENTS; CONSCIENTIOUSNESS; INTELLIGENCE; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics